Nonoperative management of colon and mesocolon injuries caused by blunt trauma: three case reports - Naa Lee; Euisung Jeong; Hyunseok Jang; Yunchul Park; Younggoun Jo; Jungchul Kim (Journal of Trauma and Injury)
The therapeutic approach for colon injury has changed continuously with the evolution of management strategies for trauma patients. In general, immediate laparotomy can be considered in hemodynamically unstable patients with positive findings on extended focused assessment with sonography for trauma. However, in the case of hemodynamically stable patients, an additional evaluation like computed tomography (CT) is required. Surgical treatment is often required if prominent mesenteric extravasation, free fluid, bowel infarction, and/or colon wall perforation are observed. However, immediate intervention in hemodynamically stable patients without indications for surgical treatment remains questionable. Three patients with colon and mesocolon injuries caused by blunt trauma were treated by nonoperative management. At the time of admission, they were alert and their vital signs were stable. Colon and mesocolon injuries, large hematoma, colon wall edema, and/or ischemia were revealed on CT. However, no prominent mesenteric extravasation, free fluid, bowel infarction, and/or colon wall perforation were observed. In two cases, conservative treatment was performed without worsening abdominal pain or laboratory tests. Follow-up CT showed improvement without additional treatment. In the third case, follow-up CT and percutaneous drainage were performed in considering the persistent left abdominal discomfort, fever, and elevated inflammatory markers of the patient. After that, outpatient CT showed improvement of the hematoma. In conclusion, nonoperative management can be considered as a therapeutic option for mesocolon and colon injuries caused by blunt trauma of selected cases, despite the presence of large hematoma and ischemia, if there are no clear indications for immediate intervention.